Brachial Plexus Palsy and Cortical Dysplasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Researchers at the Miami Children's Hospital report 2 infants with obstetrical brachial plexus palsy, ipsilateral leg weakness, and contralateral motor cortical dysplasia.